Keragaman dan Kekerabatan Macaranga Pulau Bangka - Nurtjahya, Eddy; Rani, Melia Panca; Ardiyani, Marlina (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2023)
Macaranga Thou. (Euphorbiaceae) is the largest genus which is known as a pioneer on disturbed land due to mining, agriculture, and settlements. The study aims to record diversity and analyze Macaranga relationships on Bangka Island and compare them with those in the Sundaland region. It was carried out in July – Desember 2018 in four habitat types: hills, lowland forest, peat swamp forest, and open land, with each in five different villages. Specimens were identified with the collections of Herbarium Bangka Belitungense and Herbarium Bogoriense. Leaf samples for molecular tests used the teabag method, DNA analysis with a combination of primers ITS4 and ITS5, and analysis using Maximum Likelihood. The five species documented are M. bancana, M. gigantea, M. javanica, M. pruinosa, and M. trichocarpa. All species grow mostly in lowland forests and hill forests, M. pruinosa is only found in peat swamp forests. M. bancana and M. pruinosa are closely related to Macaranga in the Malay Peninsula, M. trichocarpa is close to the species in Borneo, while M. javanica is not known to be related to either the Malay Peninsula or Borneo because there are no comparable sequences. M. gigantea does not show strong genetic differences from the Malay Peninsula or Borneo.